Tatake: The spatial twist of anime in the social protest's context - Vargas Vargas, Joaquín (2022)
Walking through the streets of the center of Santiago de Chile after the social revolt of October 2019, one can see the mural interventions that commemorate and denounce state violence, confronting the government's silence and censorship on the human rights violations during those months. Among these, it is not uncommon to see urban art that refers to consumer culture, especially Japanese animation series (anime) and manga (Japanese comics) made by organizations such as Otaku Antifascista or Tatakae Chile. However, the phenomenon draws attention because it is replicated not only in the context of the protest in Chile but also in countries like Peru and Bolivia, where anime fans, widely known as otakus, build a new language of social protest. This essay reflects on this articulation, evaluating the spatial displacement of the otaku referent from its consumption in private (closed) spaces to its use in public ones (as a political message), following the logic of the spatial theory.